Addressing Email Loss with SureMail: Measurement, Design, and Evaluation - Agarwal, Sharad; Joseph, Dilip; Padmanabhan, Venkat (Microsoft, 2006)
We consider the problem of silent email loss in the Internet, where neither the sender nor the intended recipient is notified of the loss. Based on a detailed measurement study over three months, we find the silent email loss rate to be 0.71 to 0.91%. This suggests that the problem is non-negligible, especially since silent loss can impose a high cost. To address this problem, we present SureMail, a system that augments the existing SMTP-based email system with a notification overlay to make intended recipients aware of email they might be missing. A notification is a short, fixed-format fingerprint of an email message constructed so as to preserve sender and recipient privacy, and to prevent spoofing by spammers. Our design also avoids dependence on any special support from the email infrastructure or modifications to emails themselves, or on a PKI for email users. It also places minimal demands on users, by automating the tasks of generating, retrieving, and verifying notifications, thus only presenting valid notifications of lost email to users. Based on our prototype implementation of SureMail, we demonstrate its effectiveness in notifying recipients when they suffer silent email loss.